O problema da normatividade na fenomenologia hermenêutica de Martin Heidegger - Dietrich, Gabriel Henrique (2014)
In Being and Time, Heidegger places the question of the meaning of being in order to develop the project of fundamental ontology. Generically, the meaning of being can be characterized as an ontological standard from which the entities present with certain ontological identities. Because the human being is the entity that understand the various senses of being, the project of elaborating the fundamental ontology unfolds initially in terms of the analytic of existence, encompassing both divisions of Being and Time. Recently, the question of the meaning of being has been interpreted as tantamount to question the intelligibility of something. For this interpretation, all intelligibility involves conditions of satisfaction from which something can be identified as something. In other words, with the recognition of norms that establish the criteria for entities s identity are possible understand something as something. More precisely, Robert Brandom attributes to the analytic s of the existence a commitment to what he termed "pragmatism normativist". Generically, the normative pragmatism is characterized by recognizing that the normativity s domain is more basic than the factual one and that standards need not be present linguistically formulated as principles or rules. The pragmatist reception have trouble in linking themes and concepts of Division II of Being and Time to question on intelligibility of something. Precisely in order to overcome this limitation interpretive, John Haugeland presented what he called "transcendental existentialism". In general, this consists of existentialism link to existential death with truth qua unveiling. Thus, the intelligibility of beings is elucidated from the existing commitment to have their own identities and the rules that structures it. Following the interpretation of Haugeland, Crowell interpreted the analytic of existence from the horizon of transcendental philosophy. Thus, the themes of Division II are interpreted in light of their contribution to the normativity of meaning. To do so, we must recognize the role that the irreducible first-person perspective would play in Being and Time. The overall objective of this dissertation is to reconstruct and articulate receptions binding sense with normativity. Furthermore, with the open receptions for these interpretative perspective Heidegger seeks to shed light on the issues of the second division of Being and Time.